URINARY SOMATIC ANGIOTENSIN CONVERTING ENZYME AND SOLUBLE N-DOMAIN ISOFORMS (90 AND 65KDA) EXPRESSION AND CORRELATION WITH DIFFERENT NUTRITIONAL STATUS/CARDIOVASCULAR RISK PROFILE. (April 2021) - Casarini, Dulce Elena; Cruz, Nayara; Oliveira, Lilian; Fernandes, Fernanda; Mill, José
Abstract: Objective: Angiotensin converting enzyme (ACE) has been involved in physiopathology of several diseases including hypertension, diabetes, obesity and metabolic syndrome. The somatic ACE weights from 130–190 KDa and presents N- and C-domains. Two soluble N-domain isoforms have been described in human urine, weighting 65 and 90KDa. Studies have supported that N-domain ACE with 90KDa is a biomarker for hypertension, pre-eclampsia and inflammation. We evaluated the expression of somatic ACE and soluble N-domain isoforms (90 and 65KDa) in urine of children and adolescents with different nutritional status and cardiovascular risk profile. Design and method: The participants aged from 6 to 19 years were classified into four groups according to their BMI percentile; underweight (n = 51), normal weight (n = 53), overweight (n = 53) and obese (n = 49). Waist-height-ratio (WHtR) was used to assess cardiovascular risk profile dividing the participants into normal risk (n = 105) and high risk (n = 101). The urines were concentrated 10-fold and dialyzed with Tris-HCl pH 8 and pure water. Then, we performed western blot analysis using 50 mg of lyophilized urinary protein. ACE expression was proved against the polyclonal antibody Y1. Protein detection was performed by chemiluminescent and analysis was done in Image Labâ (BioRad) software utilizing total protein stain for normalization. Results: ACE expression is augmented in obese children when compared with normal weight children (0.09 vs 0.53 arbitrary units, p = 0, 04). The higher cardiovascular risk group also presented increased expression of ACE (0.27 vs 0.09 arbitrary units, p = 0.046). The 90KDa N-domain isoform is frequently found in the high cardiovascular risk children (p = 0.02). Additionally, according to Spearman correlation test, the expression of 90KDa N-domain isoform correlates positively with waist circumference (cm), WHtR, BMI percentile and Z-score of BMI. Conclusions: Increased ACE expression in obese children contributes to higher cardiovascular risk once this enzyme biosynthesizes Angiotensin II which promotes blood pressure increase, sympathetic nervous system activation and release of glucocorticoids from adrenal gland. ACE expression is also augmented in children with high cardiovascular risk. Presence of 90 KDa N-domain ACE in urine of children and adolescents is a biomarker of poor prognostic for cardiovascular disease in childhood obesity.